Suksesi mikroalgae pada insulasi dingin san dinding luar tangki LNG/LPG - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT: Corrosion on metal equipment of natural gas industries, which is caused by microorganism activity, is preceded by the growth of pioneer microorganisms and then followed by the growth of other organisms. The purposes of this research are to reveal microalgae succession process on cold insulation and the outer wall of LNG/LPG tank, as well as to identify the microalgae that involved in the process. The microalgae samples were obtained from PT Badak NGL Bontang, East Kalimantan. Microalgae isolation and identification were done in Laboratory of Microbiology, Center for Biotechnology Study, Gadjah Mada University. Samples were taken from four locations, i.e., upper tank (dome), wet lower tank, dry lower tank and cold insulation, which have the highest microalgae growth. Sampling was done using community change ecological method within 1 m2 plot. Sample plots were clean. The sampling were done every two weeks until two month. The obtained microalgae were identified based on morphological observation according to Humm (1980). Molecular analysis to detect the microalgae community was implemented by using RISA (Ribosomal Intergenic Spacer Analysis). Several kinds of microalgae were found two weeks after cleaning. There were found 4, 2, 4 and 3 genera respectively on dome, wet lower tank, dry lower tank and cold insulation. Fourweeks after cleaning, on dome, wet lower tank, dry lower tank and cold insulation were found 3, 2, 2 and 2 genera respectively. Six weeks after cleaning, there were found 3, 4, 1 and 2 genera respectively on dome, wet lower tank, dry lower tank and cold insulation. In the end of the observation, eight weeks after cleaning, on dome, wet lower tank, dry lower tank and cold insulation were found 4, 4, 3 and 4 genera respectively. After identification, it was found that 61% microalgae not identified. Thirty nine percent microalgae were classified in to the genera of Chroococcus, Lyngbya, Gloeocapsa, Oscillatoria, Gloeotrichia and Trentepohlia. Molecular analysis shows that for some DNA bands. Several kinds of bands were identified two weeks after cleaning. There were found 4, 3, 4 and 4 bands respectively on dome, wet lower tank, dry lower tank and cold insulation. Four weeks after cleaning, on dome, wet lower tank, dry lower tank and cold insulation were found 3, 3, 2 and 3 bands respectively. Six weeks after the cleaning, there were found 3, 2, 2 and 1 bands respectively on dome, wet lower tank, dry lower tank and cold insulation. In the end of the observation, eight weeks after cleaning, on dome, wet lower tank, dry lower tank and cold insulation were found 2, 2,1 and 1 bands respectively. Both morphological observation and molecular analysis indicate the occurrence microalgae succession. The genera of Gloeocapsa were found to be the pioneer microalgae which become dominant at the end of the observation at all sampling locations.